Implementation of Transformational Leadership to Improve School Achievement - Siti Maftuhatur Rohmah; Fahri Andriyan; Didit Darmawan (Global Education Journal, 2026)
School achievement is the main indicator that reflects the quality of education delivery in an institution. The achievement of optimal achievement requires a strategic role from the principal as a leader to manage and develop the various potentials possessed by the school. This study aims to examine the application of transformational leadership by school principals to improve school achievement, as well as analyze the factors that affect the success of the implementation of transformational leadership. The method used in this study is a literature study that collects and analyzes various sources of information relevant to the topic of the study. The results of the study show that the application of transformational leadership through four main components, namely ideal influence, inspirational motivation, intellectual stimulation, and individual consideration, plays a significant role in creating a positive work environment, increasing teacher motivation and performance, improving the quality of the learning process, and encouraging the active involvement of all school residents to achieve common goals. The success of the implementation of this leadership style is influenced by factors such as the ability of the principal to build cooperative relationships, develop a clear vision and mission, the availability of adequate resources, and support from the surrounding environment.